IMPROVEMENT OF FOOD INTAKE IN MALE VOLLEYBALL ATHLETES AFTER NUTRIRION COUNSELING - Renamastika, Stephani Nesya; Permadi, M Rizal; Purnasari, Galih (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Introduction: Proper macronutrient intake, including carbohydrates, protein, and fat, is essential for promoting overall well-being and enhancing physical performance. Adequate food intake is helpful to replenish energy stores during physical activities such as training, competition, or recovering.Purpose: This study was conducted to investigate the energy and macronutrient intake habits of male volleyball players who received nutritional counseling as an intervention.Methods: This study was an experimental with one group pre and post test design, conducted on ten male volleyball athletes aged 16-22 years in Jember Regency. The data collection included anthropometric measurements, hydration state, biochemical status, and the the participant's food intake. Data of food intake was gathered on two occasions, specifically prior and following the intervention using 24-hour food recall questionnaire.Result: There was no significant difference in the mean intake of energy, protein, fa t, and carbohydrates before and after the intervention (p>0.05), however there was a tendency towards an increase in the mean intake of energy, protein, and carbohydrates after the intervention. Conclusion: Nutritional counseling proves beneficial in enhancing the energy and macronutrient consumption of male volleyball athletes, although not statistically significant.